The impact of on-site educational outreach on recreational users' perceptions of aquatic invasive species and their management. Issue 8 (14th September 2017) - Sharp, Ryan L.; Cleckner, Lisa B.; DePillo, Sarah
Abstract: Aquatic invasive species (AIS) present a great challenge to ecosystems around the globe, and controlling AIS becomes increasingly difficult when the potential vectors are related to recreational activities. An approach combining education and outreach efforts to control AIS may be the best course of action. A survey was designed to measure public perceptions, knowledge of, and attitudes towards AIS, as well as public support for various management actions. Surveys were administered during the summer of 2013 at two boat launches where one launch had active outreach the previous summer and one that did not. A total of 400 surveys were completed with a response rate of 89%. There was support for most proposed management options, and respondents understood the urgency of managing AIS. There was a difference between the launches in how people responded, highlighting that educational programming may need to be tailored for specific recreational uses and recreational settings.